Pengaruh Brand Image, Harga Dan Promosi Penjualan Terhadap Minat Beli Di Transmart - Sumarwan, Romie Giri Ginanjar; Herlina, Listri (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to analyze the influence of Brand Image, Price, and Sales Promotion on consumer purchasing interest at Transmart. In the context of the rapidly evolving retail industry, particularly in Indonesia, these factors are crucial for understanding consumer behavior. The research employs a quantitative method with a descriptive approach, involving 100 respondents from the productive population in Bandung Regency. Data were collected through an online questionnaire. The analysis results indicate that brand image has a positive and significant effect on purchasing interest, while price does not show a significant impact. Sales promotion also proves to have a positive influence on purchasing interest. Overall, the regression model reveals that 39.5% of the variation in purchasing interest can be explained by brand image, price, and sales promotion. This research provides valuable insights for retail managers in formulating effective marketing strategies to enhance consumer purchasing interest.